Studenci z Polski na uniwersytetach niemieckich w późnym średniowieczu - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2026)
The article aims to discuss the state of research on the issue of student mobility from Polish lands, including Royal Prussia, to universities in the Holy Empire’s lands in the late Middle Ages. In my analyses, I also include territories under the rule of the Teutonic Order in the 15th century due to their ties with Poland. The most popular destination for Polish youth was the University of Prague, founded by King Charles IV of Luxembourg as the first university in the Holy Empire. The Czech university was an interesting alternative to Italian and French universities, not only for economic reasons. Other destinations to which students from Poland went were universities in Erfurt, Heidelberg, Cologne, Vienna, Würzburg, and Leipzig, as well as in Tübingen, Rostock, Greifswald, Freiburg im Breisgau, Ingolstadt, Mainz. The municipal authorities and cathedral chapters contributed to these and no other destinations, conducting an appropriate scholarship policy. Significant in this context are the relatively numerous scholarships funded from the first half of the 15th century by Prussian and Livonian cities. The students were dominated by the sons of townspeople, both from larger cities and smaller centres. A few peasants and monks, especially Dominicans and Cistercians, were left to study. In the article, I also touch on student peregrinations of princes from the Piast dynasty